'The only safe haven of refuge in all the world': Paris, Indian 'revolutionaries' and imperial rivalry, c. 1905–40. (August 2019) - Marsh, Kate
Focusing on British Indian subjects who travelled to France in the early twentieth century and who resided in Paris, this article argues that these migrants occupied a position that was simultaneously privileged and invidious. It urges that closer attention be paid to the group for two reasons. First, British Indians in Paris were able to negotiate contentious and potentially hazardous political situations according to context and audience, sometimes mobilising their status as British subjects as a means of achieving limited preferential treatment from the French state, at other times making use of a certain conception of Frenchness to garner support among socialist and anti-imperial movements. Second, the policing of the group reveals collaboration and competition between imperial nation-states and between different anti-colonial movements, analysis of which can nuance the growing body of historical research on the policing of foreigners and colonial subjects in Europe.